Arts-Based Research and the Practice of Freedom in Education : Reflections from a Doctoral Course - Fellner, Gene (Bold Visions in Educational Research, 2024)
Arts-Based Research and the Practice of Freedom in Education advocates for the inclusion of arts-based research in doctoral education programs and, indeed, in educational programs at all levels. The doing of art to investigate ideas, situations, and experiences embraces bell hooks' concept of education as the practice of freedom, a practice in which everyone can learn and every voice counts. Through the use of photography, collage, painting, sculpture, textile arts and dance, 10 current and former doctoral students who had enrolled in an arts-based research course show and write about how arts-based methods enriched their educational experiences, celebrated their wholeness by dissolving the barriers between their scholar-artist-teacher-activist selves, and affirmed the inner-artist even in those who doubted they had one. Furthermore, their work establishes that arts-based research can reveal dimensions of experience that elude traditional research methods. Contributors are: Michael Alston, Kelly Bare, Shawn F. Brown, Nicholas Catino, Christopher Colón, Abby C. Emerson, Gene Fellner, Francie Johnson, Rendón Ochoa, Mariatere Tapias and Natalie Willens.